How the theory of information and journalism ethics contributes to the ethics of public relations: six principles from the dialogue between codes of ethics and Luka Brajnović's legacy. - Kolić Stanić, Matilda (Church, Communication & Culture, 2020)
The ethics of public relations (PR), irrespective of how many different theoretical and practical approaches have contributed to it, still has a gap to fill concerning the role of human person. This study attempts to fill this gap by introducing into PR theory the intellectual legacy of Brajnović (1919–2001), a pioneer of both journalistic ethics and information theory. The main goal of the study is to arrive at the formulation of the principles that could guide PR, based on the human dignity of each person engaged in PR communication. This goal is reached by applying the method of content analysis to two sources: (1) to 13 ethical codes that were designed as guidelines for members of 18 PR associations, both national and international, from the European Union and the United States of America; and (2) to a sample of texts from Brajnović's written legacy. As the result, six principles of PR ethics emerge: (1) Truthfulness, (2) Transparency, (3) Professional Integrity, (4) Professional Competence, (5) Loyalty, and (6) Social Responsibility. The conducted research has shown that the concepts of human person and information, as they are explicated in Brajnović's theoretical work, can be applied to ethics of PR.